STRATEGI KOMUNIKASI DALAM MEMPERTAHANKAN EKSISTENSI BATIK TULIS GARUTAN - Zikri Fachrul Nurhadi; Haryadi Mujianto; Hardan Adha Apriana (Commed : Jurnal Komunikasi dan Media, 2022)
Batik Tulis Garutan is part of the local wisdom typical of Garut Regency which is still surviving until now. Currently, Batik Tulis Garutan is concentrated in Garut city, the average production capacity per year is 1,600 pieces. Based on the data obtained, this study intends to find out how the Garutan Batik Written House RM maintains the existence of Garutan hand-drawn batik. The purpose of this study is to explain how to define problems or opportunities, planning and programming, taking action and communication, and evaluating programs in the Communication Strategy of Rumah Batik Tulis Garutan RM. The research method used is a qualitative descriptive method. While the data collection techniques used in this study were in-depth interviews, observation and documentation. The subject of this research is the Garutan Batik Writer House Manager, who is involved in implementing the communication program planning strategy, totaling three people using snowball sampling. The result of the research shows that Rumah Batik Tulis Garutan RM has not been able to implement the implementation of the workshop program as a communication strategy in maintaining the existence of Batik Tulis Garutan. It is shown that Rumah Batik Tulis Garutan RM .in defining the problem or analyzing the situation is not enough to find out how the problem is happening, because it is more focused on the production and sale of products. In the planning and programming strategy there is a structured plan that contains goals, targets, conveys messages in an informative, persuasive and instructive manner, but there is no maximum technical arrangement, the strategy is carried out by maximizing good relations with external parties as targets and utilizing the media. Implementation is done by compiling a periodic scale, the allocation of resources. The evaluation was carried out by Rumah Batik Tulis Garutan RM based on the number of participants, with this number it can be seen that the enthusiasm of the community in supporting the implementation of the program was carried out.